2020
DOI: 10.21203/rs.2.13168/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictors of advanced fibrosis in elderly patients with biopsy-confirmed nonalcoholic fatty liver disease: The GOASIA study

Abstract: Background: The Gut and Obesity in Asia (GOASIA) Workgroup was formed to study obesity and gastrointestinal diseases in the Asia Pacific region. We aimed to 1) compare the characteristics of elderly (i.e. age ≥ 60) vs. non-elderly patients with biopsy-proven nonalcoholic fatty liver disease (NAFLD); 2) identify predictors of advanced fibrosis in elderly patients with NAFLD; and 3) assess the performance of non-invasive fibrosis scores in the prediction of advance fibrosis in the elderly population. Methods: We… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…Pitisuttithum et al . reported similar results among 1008 Asian patients with NAFLD from eight countries 9 . Age was strongly associated with NAFLD‐related fibrosis, and elderly patients (age ≥ 60 years) had a significantly higher rate of advanced fibrosis (13.3% vs 35.4%; P < 0.001).…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…Pitisuttithum et al . reported similar results among 1008 Asian patients with NAFLD from eight countries 9 . Age was strongly associated with NAFLD‐related fibrosis, and elderly patients (age ≥ 60 years) had a significantly higher rate of advanced fibrosis (13.3% vs 35.4%; P < 0.001).…”
mentioning
confidence: 55%
“…Regarding risk factors for fibrosis, Pitisuttithum et al . reported that female gender and hypertension were predictive of advanced fibrosis in a large cohort of elderly subjects 9 . Chen et al .…”
mentioning
confidence: 99%
“…Third, this study is limited by the overrepresentation of females (72%) in the health examination database, which may be seen as a selection bias to our study. However, this may be explained by a previous study that indicated an association between NAFLD and female sex (7). Nevertheless, there is con icting data about the association of sex and prevalence of NAFLD (27), since the true prevalence of NAFLD is di cult to predict.…”
Section: Strengths and Limitationsmentioning
confidence: 96%
“…There have been previous studies (6,7) regarding the association between certain risk factors for NAFLD, such as female sex, hypertension, and serum glycated hemoglobin (HbA1c). Elderly patients have a higher risk of liver-related disease and death (2).…”
Section: Introductionmentioning
confidence: 99%
“…Mcpherson and colleagues also suggested that 2.0 of low COI in 65 years or older [80]. On data of 1008 patients with NAFLD from nine centers across eight countries (The Gut and Obesity in Asia (GOASIA) Workgroup), NITs such as APRI, NFS, and FIB-4 index had a lower specificity in elderly (AUROC 0.62-0.65) [82]. Female (OR: 3.21; 95% CI 1.37-7.54] and hypertension (OR 3.68; 95%CI 1.11-12.23) were predicting factors for advanced fibrosis in the elderly [82].…”
Section: Drawbacks Of Fib-4 Indexmentioning
confidence: 99%